Erosion Response of High-Velocity Oxy-Fuel Sprayed Marble Dust-NiCr Coatings. Issue 4 (2nd October 2022) - Nayak, Sandip Kumar; Satapathy, Alok; Mantry, Sisir; Besra, Laxmidhar
Abstract : In the present research, raw marble dust (an ornamental stone waste) with and without pre-mixing of nickel chrome (NiCr) powder are used as the feedstock material to deposit overlay coatings on the mild steel substrates through HVOF spraying technique. The physical as well as mechanical characterizations of the deposited coatings in terms of deposition efficiency, adhesion strength, coating thickness and micro-hardness are done at controlled laboratory conditions. To get an insight to the erosion behavior of the deposited coatings, high temperature solid particle erosion trials on them are carried out as per ASTM G76 considering the test parameter combinations obtained from Taguchi's L16 orthogonal array. On analyzing the experimental outcomes, impact velocity, NiCr content in the feedstock, erodent temperature and impingement angle are found to be sequentially significant in terms of affecting the wear loss of the coatings. Based on the findings from the analysis, further experimentations are conducted at different levels of the significant control factors to ascertain their effects on the wear rate more precisely. The micrographs of the worn surfaces taken using a scanning electron microscope are studied to identify the possible damage mechanisms causing the erosion loss. GRAPHICAL ABSTRACT: UF0001